Family connections programme: Optimising parenting in marginalised families efforts - Pradipta Christy Pratiwi; Siti Nuzulia; Anna Undarwati; Lukki Lukitawati; Ifa Nurhayati (University of Merdeka Malang, 2024)
Family is the main pillar of mental health’. It is undeniable that various mental health problems originate from family factors, such as depression, suicidal ideation, and personality disorders. We found that there was a poor quality of relationships between parents and children that triggered prolonged psychological conflict. So, the need for psychoeducation on the role of parents in child development among marginalised communities emerged. The purpose of this service is to increase awareness of the importance of the quality of parenting psychologically in marginalized families in Semarang City. The method of service carried out is psychoeducation and support groups. The participants of this service were 34 people. The implementation of the service was divided into two. First, parenting psychoeducation. The second activity was a support group on the role and importance of the quality of the relationship between parents and children. Case cards were used during the discussion in the group, this instrument helped the discussion without removing the opportunity to convey their experiences in the family authentically. The evaluation was done qualitatively. From this activity, it was found that there was a transfer of learning in simple knowledge and skills, while beliefs were difficult to change, such as that children should be physically punished when parents are angry. This is a finding that can be explored further in research or work with families.